Distance Learning Course Design Expectations in China and the United Kingdom. Issue 4 (1st October 2016) - Xu, Jingjing; Rees, Terri
ABSTRACT: This article provides insight into different expectations between Chinese and British academic culture for distance learning. The article is based on a pedagogic research project, a case study, and is centered on a distance learning course in maritime law proposed by a British university for a university in China. Some important commonalities and gps between perceptions of deliverers and receivers of the proposed course were identified. There were important differences between Chinese and UK respondents about the value of open educational resources, the sequential access to course materials, the type of technologies that were important for delivery of content and for communication, the value of peer assessment, and the time expectations for feedback. Recommendations are suggested for bridging the cultural gaps in distance learning between a British and Chinese context.